Cell-cycle involvement in autophagy and apoptosis in yeast. (January 2017) - Azzopardi, Maria; Farrugia, Gianluca; Balzan, Rena
Highlights: A common set of factors may be responsible for cell proliferation and death. Homologues of these molecular players exist in yeast and metazoans. DNA damage and replication stress cause cell-cycle checkpoint activation. Activated checkpoints may induce autophagy to mediate cell survival or death. Deficiency in checkpoints results in cell-cycle dysregulation and cell death. Abstract: Regulation of the cell cycle and apoptosis are two eukaryotic processes required to ensure maintenance of genomic integrity, especially in response to DNA damage. The ease with which yeast, amongst other eukaryotes, can switch from cellular proliferation to cell death may be the result of a common set of biochemical factors which play dual roles depending on the cell's physiological state. A wide variety of homologues are shared between different yeasts and metazoans and this conservation confirms their importance. This review gives an overview of key molecular players involved in yeast cell-cycle regulation, and those involved in mechanisms which are induced by cell-cycle dysregulation. One such mechanism is autophagy which, depending on the severity and type of DNA damage, may either contribute to the cell's survival or death. Cell-cycle dysregulation due to checkpoint deficiency leads to mitotic catastrophe which in turn leads to programmed cell death. Molecular players implicated in the yeast apoptotic pathway were shown to play important roles in the cell cycle. These include the metacaspase Yca1p, the caspase-like protein Esp1p, the cohesin subunit Mcd1p, as well as the inhibitor of apoptosis protein Bir1p. The roles of these molecular players are discussed.